2019
DOI: 10.1056/nejmoa1816047
|View full text |Cite
|
Sign up to set email alerts
|

Avelumab plus Axitinib versus Sunitinib for Advanced Renal-Cell Carcinoma

Abstract: BACKGROUND In a single-group, phase 1b trial, avelumab plus axitinib resulted in objective responses in patients with advanced renal-cell carcinoma. This phase 3 trial involving previously untreated patients with advanced renal-cell carcinoma compared avelumab plus axitinib with the standard-of-care sunitinib. METHODS We randomly assigned patients in a 1:1 ratio to receive avelumab (10 mg per kilogram of body weight) intravenously every 2 weeks plus axitinib (5 mg) orally twice daily or sunitinib (50 mg) ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
1,713
4
54

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 2,023 publications
(1,928 citation statements)
references
References 30 publications
47
1,713
4
54
Order By: Relevance
“…The main purpose of the four‐tier model was the separation of prognosis in patients in the IMDC intermediate‐risk group in the immunotherapy era. Within a year, we need to select “avelumab/pembrolizumab + axitinib” or “nivolumab + ipilimumab” for the patients in the intermediate/poor risk groups . Currently, the recommendation of optimal treatment selection in those patients is not available.…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of the four‐tier model was the separation of prognosis in patients in the IMDC intermediate‐risk group in the immunotherapy era. Within a year, we need to select “avelumab/pembrolizumab + axitinib” or “nivolumab + ipilimumab” for the patients in the intermediate/poor risk groups . Currently, the recommendation of optimal treatment selection in those patients is not available.…”
Section: Discussionmentioning
confidence: 99%
“…The study design and patient eligibility criteria have been described in detail previously . This was a multicenter, randomized, open‐label, phase 3 trial comparing avelumab + axitinib with sunitinib.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary data from a single‐arm phase 1b study of avelumab + axitinib in treatment‐naive patients with advanced RCC showed a manageable safety profile and encouraging antitumor activity, with an objective response rate (ORR) of 58% . The randomized phase 3 JAVELIN Renal 101 clinical trial of avelumab + axitinib vs sunitinib in previously untreated patients with advanced RCC demonstrated longer PFS (median, 13.8 vs 7.2 months; stratified hazard ratio [HR], 0.61; P < 0.001) and higher ORR (55.2% vs 25.5%) with the combination vs sunitinib in patients with PD‐L1+ tumors . PFS and ORR benefits were also observed in patients irrespective of PD‐L1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy has changed the landscape of treatment of metastatic renal cell carcinoma (mRCC) since nivolumab, a programmed cell death protein‐1 (PD‐1) inhibitor, was approved for vascular endothelial growth factor (VEGF)–refractory mRCC in November 2015 . The first immune checkpoint inhibitor (ICI) combination regimen, nivolumab and ipilimumab, was recently approved for first‐line intermediate or poor risk mRCC, and results from ongoing trials of ICI and anti‐VEGF combination regimens have been very promising . Given the increasing number of treatment options for patients with mRCC, including several ICI‐based regimens, it is becoming increasingly important to identify risk factors that make patients with mRCC more likely to respond to ICI.…”
Section: Introductionmentioning
confidence: 99%